Photothermally Reconfigurable Biomimetic Photonic Structures Prepared via Crystallization of Polydopamine-Incorporated Core–Shell Nanoparticles - Oh, Chi Yeung; Kim, Jong Sik; Shim, Tae Soup (Advanced Optical Materials, 2024)
Some creatures have periodic nanostructures and chromophores in their flexible organs that allow them to control the color and shape of their skin. Artificial photonic structures that can mimic the aforementioned ability of these natural structures are researched extensively. In this study, polydopamine-incorporated core–interlayer–shell (CIS-PDA) nanoparticles capable of shape reconfiguration and expressing vivid structural colors are designed. These nanoparticles can be readily assembled to produce colloidal photonic crystals (CPhCs) and can exhibit vivid structural colors by virtue of their light-absorbing capability. Soft CPhC films prepared with these nanoparticles undergo stable elastic deformation at 15% strain and exhibit mechanochromic properties. Specifically, the PDA in the CIS nanoparticles can absorb broadband light and exhibit a photothermal effect resembling that of melanosomes in living organisms, which enables self-healing between multiple CPhC films. Due to their favorable properties, the CPhC films prepared in this study represent promising photothermally reconfigurable photonic materials. Moreover, arbitrarily shaped 2D or 3D surfaces are conformally coated with the films via microimprinting or vacuum wrapping, courtesy of the reconfigurability of these films. These findings suggest that CPhC films prepared with CIS-PDA nanoparticles can be used as form-free mechanochromic strain sensors and nonfading optical films for industrial products.
Keywords: Colloidal photonic crystals; Core-shell nanoparticles; Periodic nanostructure; Photonic crystal films; Photonic structure; Photothermal effects; Photothermally; Polydopamine; Reconfigurable; Structural color; colloidal photonic crystals; core–shell nanoparticles; photothermal effect; polydopamine; self-healing materials